Can AI Improve Early Detection of Age-Related Macular Degeneration? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Age-related macular degeneration (AMD) represents a significant and growing challenge in ophthalmology. As a leading cause of irreversible vision loss among ...
Keywords: AI in Ophthalmology; Improve; Early; Detection; Artificial Intelligence; Machine Learning; Deep Learning